Neuropathic-Like Pain Symptoms in a Community-Dwelling Sample with or at Risk for Knee Osteoarthritis. Issue 1 (30th May 2019) - Terry, Ellen L; Booker, Staja Q; Cardoso, Josue S; Sibille, Kimberly T; Bartley, Emily J; Glover, Toni L; Vaughn, Ivana A; Thompson, Kathryn A; Bulls, Hailey W; Addison, Adriana S; Staud, Roland; Hughes, Laura B; et al.
Abstract: Objective: To characterize neuropathic-like pain among individuals with or at risk for knee osteoarthritis. Subjects: One hundred eighty-four individuals who self-identified as non-Hispanic black or non-Hispanic white and presented with unilateral or bilateral knee pain. Design: Neuropathic-like pain was assessed using the painDETECT, and those with high vs low neuropathic-like pain were compared on clinical pain, psychological symptoms, physical function, and quantitative sensory testing. Analyses were unadjusted, partially and fully adjusted for relevant covariates. Results: Thirty-two (17.4%) participants reported experiencing neuropathic-like pain features above the painDETECT clinical cut-score. The neuropathic-like pain group reported significantly greater pain severity on all measures of clinical pain and higher levels of psychological symptoms when fully adjusted for covariates, but no differences emerged for disability and lower extremity function. The neuropathic-like pain group also reported greater overall heat pain ratings during the heat pain threshold and increased temporal summation of heat pain in the fully adjusted model. Additionally, those with neuropathic-like pain symptoms reported greater painful after-sensations following heat pain temporal summation in all analyses. No significant group differences in pressure pain threshold emerged at any of the testing sites. In contrast, temporal summation of mechanical pain was significantly greater at both the index knee and the ipsilateral hand for the neuropathic-like pain group in all analyses. Conclusions: Participants with or at risk for knee osteoarthritis who reported high neuropathic-like pain experienced significantly greater clinical pain and increased heat and mechanical temporal summation at the index knee and other body sites tested, suggesting central sensitization.